Analisis Respons Transien Motor DC terhadap Perubahan Beban Menggunakan Kontrol PI - Michael Oklando Sihotang; Takwa Padang; Roihan Parli Lubis; Desman Jonto Sinaga; Arwadi Sinuraya (JURNAL ILMIAH NUSANTARA, 2026)
. This study analyzes the transient response of a DC motor to load variations using a Proportional-Integral (PI) controller implemented through MATLAB/Simulink simulation. The DC motor is modeled using a transfer function and tested under three conditions: without controller, with PI controller tuned by PID Tune (PI1 and PI2), and with a step load disturbance applied at seconds. Performance is evaluated based on rise time, peak time, overshoot, settling time, steady-state error, and recovery time. The results show that the system without control is highly sensitive to load changes, exhibiting a large steady-state error and a significant speed drop. The application of PI control improves system stability and accuracy; PI1 reduces the steady-state error to 1.65% (no-load) and 2.71% (with load) with minimal overshoot, while PI2 provides faster response with very low steady-state error (0.28% no-load and 0.27% with load) at the expense of slightly higher overshoot. Overall, PID Tune is effective in generating stable PI parameters, where PI2 achieves the best performance in response speed and accuracy, and PI1 is more favorable in minimizing overshoot.